2017
DOI: 10.1371/journal.pone.0184762
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal bacterial load as a marker for rapid and easy diagnosis of invasive pneumococcal disease in children from Mozambique

Abstract: BackgroundCurrent diagnostic methods for detection of Streptococcus pneumoniae in children with suspected invasive pneumococcal disease have limitations of accuracy, timeliness, and patient convenience. This study aimed to determine the performance of pneumococcal load quantified with a real-time polymerase-chain reaction in nasopharyngeal samples to diagnose invasive pneumococcal disease in children.MethodsMatched case-control study of patients <5 years of age with invasive pneumococcal disease admitted to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…High pneumococcal density in the nasopharynx has been linked to pneumococcal pneumonia and invasive pneumococcal disease, and investigated as a potential diagnostic tool (Baggett et al, 2017;Brotons et al, 2017). The present study provides new insights into pneumococcal density during a carriage episode, highlighting the fact that carriage is a dynamic process, affected by multiple factors including antibiotic exposure and URTIs, as well as the presence of co-colonizing pneumococcal serotypes.…”
Section: Discussionmentioning
confidence: 79%
“…High pneumococcal density in the nasopharynx has been linked to pneumococcal pneumonia and invasive pneumococcal disease, and investigated as a potential diagnostic tool (Baggett et al, 2017;Brotons et al, 2017). The present study provides new insights into pneumococcal density during a carriage episode, highlighting the fact that carriage is a dynamic process, affected by multiple factors including antibiotic exposure and URTIs, as well as the presence of co-colonizing pneumococcal serotypes.…”
Section: Discussionmentioning
confidence: 79%
“…Two studies in Vietnam found pneumococcal NP density among children with radiographicallyconfirmed pneumonia was significantly higher than density among healthy controls and children with acute lower respiratory tract infection [9,10]. Studies in South Africa and Mozambique also found higher colonization density among children with IPD compared to controls [8,11]. The colonization density among PERCH cases in Thailand was lower than the density among cases without microbiologically-confirmed pneumococcal disease at other PERCH sites, suggesting that pneumococcal disease may be less common among those presenting to hospital with severe pneumonia in Thailand compared to the other sites.…”
Section: Plos Onementioning
confidence: 99%
“…Prevalence of pneumococcal colonization is usually much higher in low-and middleincome countries [6], and the first acquisition happens at a younger age compared with highincome settings [3]. Although detecting pneumococcus in the nasopharynx or oropharynx of a child with pneumonia does not indicate an etiologic role, the density of colonization has been associated with pneumococcal disease [7][8][9][10][11], and while of uncertain value for individual diagnosis, may help to improve estimates of pneumococcal pneumonia prevalence in surveillance or observational studies. However, colonization prevalence and density vary by geographic location [7][8][9][10][11], so local data are needed to understand local epidemiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we did not explicitly model carriage density, this interpretation is speculative. However, previous experimental (25) and epidemiological (37) studies have suggested that carriage density in an important factor in transmission and invasion.…”
Section: Simulated Ipdsmentioning
confidence: 97%